Application of optimization for improvement of the efficiency of louvered-fin compact heat exchangers - Souza,Diego Amorim Caetano (2016)
Abstract A few decades ago, the product development process was just based on a trial and error procedure, and the designer's experience. The need for a new way to design and manufacture more economical and sustainable products corroborates increasingly to a new vision of how to create new products for the benefit of society. Modern numerical tools allow greater knowledge about the physical phenomena involved in engineering problems and enable cost reduction with trials and time of manufacture and projection. Among the equipment that can be mentioned where numerical simulation is used, can be found heat exchangers, which are capable of accomplishing the heat transfer between two fluid medias with different temperatures. Within the range of existing exchangers, this work will address a compact model with louvered fins, widely used in the automotive and aerospace industries, mainly due to their high thermal exchange surface vs occupied volume ratio. The heat exchanger surface is analised using computational fluid dynamics tecniques disposable in the commercial code ANSYS CFX14® to reproduce the flow at service condition. Genetic optimization routines are used to increase the performance of heat exchanger. As a result, a heat transfer surface is obtained with about a 25% better performance according to the selected objective function. The dimensionless factor of the convective heat transfer coefficient (Colburn factor, j) and the friction factor (Fanning factor, f) used in (Wang et al.,1998), are employed for simulation. Experimental data are also used for validation.